Funding and University Performance: An Econometric Analysis of the Indian Public Universities - Kaur , Amanpreet (Gyan Management Journal, 2023)
Underpinning the aim of India’s National Education Policy, 2020 to devise a performance-based funding mechanism, it is pertinent to examine the impact of existing financial support on the university’s performance. Using a fixed panel data analysis, the present study investigates the influence of funding on the performance of Indian public universities over the period 2016-2020. The funding is considered in terms of the plan and non-plan grants received by universities from the central government, while performance is measured using performance parameters given by National Institutional Ranking Framework, 2021. Controlling the age, size and ownership type of university, findings reveal a significantly positive impact of funding on teaching performance, research performance and graduation outcomes of government-owned universities. Surprisingly, university’s outreach, inclusivity and peer perception have been observed to be indifferent towards central grants. Overall, the study provides valuable insights to university practitioners and policymakers for future development of the performance-funding mechanism.